Design and Fabrication of a Tractor- Drawn Multi-Crop Planter - Bedasa Waldaho; Gutu Getahun, (Indian Journal of Agriculture Engineering (IJAE), 2024)
The study was undertaken to design, fabricate multi-crop planter capable of planting maize, common bean and sorghum seeds at predetermined spacing and depths. Physical properties of seeds involved in the study were investigated to optimize the design of the planter’s components. The planter, consists of a frame, seed hopper, seed metering devices, seed tube, adjustable furrow opener, adjustable furrow covering device, and drive wheels. The investigation revealed that the sphericity of maize, common bean and sorghum were 64.8, 72.4 and 81%, respectively. Percentages of mechanically seed damaged by the planter were zero for each crops. Germination test was conducted to assess the magnitude and extent of invisible seed damage inflicted by the planter indicated mean percentage seed germination of 98.5, 94.5 and 97.3% for maize, common bean, and sorghum, respectively. The reduction in percentage germination of maize, common bean and sorghum were zero, when compared with that did not passes through the machine for all the seeds tested. Based on the above results, it is concluded that the planter can be efficiently and effectively used by the majority of the farmers and other stakeholders in the study area.